ANALISIS STUDI KOMPARATIF KEBERHASILAN BERWIRAUSAHA PADA PENGUSAHA VCO (VIRGIN COCONUT OIL) DI KABUPATEN BULELENG - PUTU RATNA KOMALA SARI; I KETUT SUARDIKA (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine how the analysis of Comparative Studies of Entrepreneurial Success in VCO (Virgin Coconut Oil) Entrepreneurs in Buleleng Regency. This research uses a qualitative approach, with data collection techniques using structured interview techniques to extract information and documentation techniques to collect a number of documents as information data material, namely sound recordings and photographs to make conclusions and data analysis. The source triangulation technique is used as a data validity technique by asking several questions to the sources so that conclusions can be drawn from the answers that have been given. Data analysis techniques used in this study using SWOT analysis, namely strengths, opportunities, weaknesses, and threats. The results of the study analyzed the entrepreneurial success of VCO products in Buleleng Regency from internal and external factors, which is said to be successful is Bali Pure VCO. From the S-O strategy where this strategy uses the strengths of the company, to take advantage of its great opportunities. This can be seen from the situation and condition of the company that is being run, which has followed the development of technology by using large industrial machines and unique packaging techniques and maintained sterilization. In addition, Bali Pure products have also innovated a lot by utilizing coconut fruit not only as pure coconut oil but also as a bath soap product with a variety of natural aromas